2017
DOI: 10.1021/acsomega.7b00670
|View full text |Cite
|
Sign up to set email alerts
|

Low Dielectric Polyetherimides Derived from Bis[4-(4-(4-aminophenoxy)-2-tert-butylphenoxy)phenyl] Sulfone and 4,4′-Bis[4-(4-aminophenoxy)-2-tert-butylphenoxy]perfluorobiphenyl

Abstract: Two diamines, bis[4-(4-(4-aminophenoxy)-2- tert -butylphenoxy)phenyl] sulfone (PSNH 2 ) and 4,4′-bis[4-(4-aminophenoxy)-2- tert -butylphenoxy)perfluorobiphenyl (PFNH 2 ), were prepared from 3- tert -butyl-4-hydroxyanisole using a four-step procedure, including two nucleophilic substitutions, demethylation, and catalytic reduction. On the basis of PSNH 2 and PFNH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…On the other hand, there is a close relationship between the dielectric constant and the density of the materials. It was postulated that the bulky biphenyl structure in BPDGE and the large volume of AE-Res effectively prevented the stacking of molecular chains in the polymer, thus reducing the density and leading to a lower dielectric constant of the materials . The d -spacing reflects the average distance between the polymer chain segments in the thermosets and also related to the free volume .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is a close relationship between the dielectric constant and the density of the materials. It was postulated that the bulky biphenyl structure in BPDGE and the large volume of AE-Res effectively prevented the stacking of molecular chains in the polymer, thus reducing the density and leading to a lower dielectric constant of the materials . The d -spacing reflects the average distance between the polymer chain segments in the thermosets and also related to the free volume .…”
Section: Resultsmentioning
confidence: 99%
“…It was postulated that the bulky biphenyl structure in BPDGE and the large volume of AE-Res effectively prevented the stacking of molecular chains in the polymer, thus reducing the density and leading to a lower dielectric constant of the materials. 57 The d-spacing reflects the average distance between the polymer chain segments in the thermosets 41 and also related to the free volume. 58 As shown in the WXRD patterns in Figure 1d, the d-spacing of AE-Res/BPDGE was enhanced in comparison with that of the MHHPA/BPDGE (4.69 vs 4.45 Å).…”
Section: Optical Properties Of the Cured Epoxy Systemsmentioning
confidence: 99%
“…Polymer Chemistry TMA results suggested that linear coefficient of thermal expansion (CTE) of the crosslinked cPI-1 and cPI-2 were 77 ppm K −1 and 61 ppm K −1 respectively, which were similar to other reported fluorinated PIs. 52 The better dimensional stability of cPI-2 was probably resulted from the closer distance between the crosslinking points in neighboring units. Besides, both cPI-1 and cPI-2 showed storage modulus higher than 2.0 GPa at room temperature (Fig.…”
Section: Papermentioning
confidence: 99%
“…Low-dielectric PIs are generally prepared via three strategies by altering the properties of diamines and dianhydrides: (i) minimizing the polarizability, (ii) imparting a high degree of free volume and (iii) eliminating water and imparting hydrophobicity to the PI. 25 The novel monomer BPBTAB has all of the aforementioned properties: the CF 3 moieties minimize the polarizability and also increase the molar volume. Furthermore, the kinkable 1,4-diisopropylbenzene unit enhances both the molar volume and flexibility, thereby decreasing polymer chain packing in the PI films.…”
Section: Dielectric Propertiesmentioning
confidence: 99%